Canada and "imperial defense" : a study of the origins of the British Commonwealth's defense organization, 1867-1919 - Preston, Richard A., 1910-2006 (Publication (Duke University. Commonwealth-Studies Center) ;, 1967)
Dr. Preston explains the vital importance of the colonies in the success of Commonwealth war efforts. His study seek the origins of British Commonwealth relationships in the history of the dominion, and especially of Canadian, military and naval developments.